An Unequal Pandemic: Vulnerability and COVID-19. (November 2021) - Robinson, Laura; Schulz, Jeremy; Ragnedda, Massimo; Pait, Heloisa; Kwon, K. Hazel; Khilnani, Aneka
This collection sheds light on the cascading crises engendered by COVID-19 on many aspects of society from the economic to the digital. This issue of the American Behavioral Scientist brings together scholarship examining the various ways in which many vulnerable populations are bearing a disproportionate share of the costs of COVID-19. As the articles bring to light, the unequal effects of the pandemic are reverberating along preexisting fault lines and creating new ones. In the economic realm, the rental market emerges during the pandemic as an economic arena of heightened socio-spatial and racial/ethnic disparities. Financial markets are another domain where market mechanisms mask the exploitative relationships between the economically vulnerable and powerful actors. Turning to gender inequalities, across national contexts, women represent an increasingly vulnerable segment of the labor market as the pandemic piles on new burdens of remote schooling and caregiving despite a variety of policy initiatives. Moving from the economic to the digital domain, we see how people with disabilities employ social media to mitigate increased vulnerability stemming from COVID-19. Finally, the key effects of digital vulnerability are heightened because the digitally disadvantaged experience not only informational inequalities but also aggravated bodily manifestations of stress or anxiety related to the pandemic. Each article contributes to our understanding of the larger mosaic of inequality that is being exacerbated by the pandemic. By drawing connections between these different aspects of the social world and the effects of COVID-19, this issue of American Behavioral Scientist advances our understanding of the far-reaching ramifications of the pandemic on vulnerable members of society.